Fibre‐optic distributed temperature sensing for characterizing the impacts of vegetation coverage on thermal patterns in woodlands. Issue 5 (7th August 2012) - Krause, S.; Taylor, S. L.; Weatherill, J.; Haffenden, A.; Levy, A.; Cassidy, N. J.; Thomas, P. A.
ABSTRACT This study presents the first application of fibre‐optic distributed temperature sensing (FO‐DTS) for analysing the impact of spatially heterogeneous vegetation patterns on the thermal conditions of an ecosystem. It analyses the spatial patterns and temporal dynamics of canopy and ground temperatures at unprecedented spatial and temporal resolution to showcase the potential as well as limitations of the FO‐DTS technology for ecohydrological applications. By using the partial rhododendron coverage of a deciduous UK woodland as a model system, FO‐DTS surveys were carried out to demonstrate the detection of different dynamic thermal patterns in the presence/absence of rhododendron (Rhododendron ponticum L). The high‐resolution temperature measurements of this study provide strong evidence for the moderating impact of rhododendron coverage on air, ground and soil temperatures in forest ecosystems, which has important implications for ecological and biogeochemical process dynamics. The results successfully demonstrate the significant potential of FO‐DTS for high‐resolution, spatially detailed, transient temperature monitoring in forest environments. The survey performance and its very efficient signal‐to‐noise ratio proves the capability of FO‐DTS networks to provide highly accurate information on temporal dynamics in spatial temperature patterns with great prospect for substantially improving spatial coverage and sensitivity of temperature observations in a range of ecological applications. Copyright © 2012 John Wiley & Sons, Ltd.